Sparse interleaved sampling for high resolution focal construct geometry X-ray tomography - Evans, J. Paul O.; Elarnaut, F.; Downes, D.; Lee, W. K.; Arnold, Emily; Rogers, Keith (Optical Society of America, 2023)
We demonstrate interleaved sampling by multiplexing conical subshells within the tomosynthesis and raster scanning a phantom through a 150 kV shell X-ray beam. Each view comprises pixels sampled on a regular 1 mm grid, which is then upscaled by padding with null pixels before tomosynthesis. We show that upscaled views comprising 1% sample pixels and 99% null pixels increase the contrast transfer function (CTF) computed from constructed optical sections from approximately 0.6 line pairs/mm to 3 line pairs/mm. The driver of our method is to complement work concerning the application of conical shell beams to the measurement of diffracted photons for materials identification. Our approach is relevant to time-critical, and dose-sensitive analytical scanning applications in security screening, process control and medical imaging.